Diagrid structures : systems, connections, details - Boake, Terri Meyer (Basel : Birkhauser, 2014)
Diagrids are load-bearing structures made of steel diagonal grids. They were first used in the great buildings of the turn of the millennium, such as the Swiss Re Tower in London ('The Gherkin') and the Hearst Magazine Tower in New York City. Dagrids owe their ensuing popularity not only to their stunning aesthetic value, but also to their very tangible benefits: lateral loading capacity, a massive saving of material, a significant gain in open, usable floor area, and increased flexibility in accommodating geometries.
Includes bibliographical references (page 178) and indexes.
Keywords: Steel, Structural -- Design and construction; Building, Iron and steel -- Design and construction; Architecture, Modern; Architecture, Domestic -- History -- 21st century; Architecture, Domestic -- History -- 20th century